The characteristics of resin/carbon composite electrode and application in selective adsorption of vanadium(IV) by capacitive deionization - Duan, Jihua; Bao, Shenxu; Zhang, Yimin (Chemical engineering research & design, 2018)
•The resin/carbon composite electrode was fabricated and applied in CDI.•Vanadium was selectively adsorbed by the composite electrode in CDI.•The mechanism of selective adsorption of vanadium was proposed.•The physical and chemical properties of composite electrode were investigated.•The performance of resin/carbon composite electrode for long time run was monitored. The characteristics and adsorption performances of three kinds of resin/mineral active carbon (Resin/AC-m) composite electrodes, the pure AC-m electrode and the resins were comparatively investigated. The Resin/AC-m composite electrodes have lower specific capacitance and higher resistance than the AC-m electrode, but their hydrophilia, specific surface areas and microspores content can be largely improved due to the addition of the resins, which is beneficial to the ions adsorption on the electrodes. The hydrated radius of VO2+ is smaller than that of Fe3+ and Al3+, then VO2+ is easier to pass through the microspores of the D860/AC-m electrode and adsorbed by the composite electrode. Thus, the D860/AC-m electrode presents the highest adsorption capacity and the strongest selectivity for VO2+, which may be resulted from the combined actions of the ion-sieve effect of the composite electrode material and the affinity of the resin for VO2+. Multiple adsorption-regeneration cycles proved that the performance of the D860/AC-m electrode can remain stable in long-term operation, indicating it may be suitable for cycle use in CDI. This study may provide a promising method for separation and recovery of ions from complex solutions.